Application of Copper Indium Gallium Selenide Thin-Film Solar Technology in Green Retrofitting of Aging Residential Buildings - Fan Lu; Mijeong Kwon; Jungsik Jang (Buildings)
The growing imperative for sustainable building retrofits has spurred significant interest in advanced photovoltaic (PV) solutions. This study evaluates the feasibility and competitiveness of incorporating CIGS thin-film photovoltaic (PV) modules into retrofit projects for aging buildings. By combining qualitative analyses of market and environmental factors with a quantitative multi-criteria index model, this research assesses CIGS performance across five critical dimensions: aesthetic, economic, safety, energy saving, and innovation. The weights assigned to each criterion were determined through expert evaluations derived from structured focus group discussions. The results demonstrate that CIGS exhibits substantial strengths in aesthetic, economic, safety, energy saving, and innovation while maintaining reasonable economic feasibility. The quantitative assessment demonstrated that CIGS thin-film solar cells received the highest overall score (88.92), surpassing silicon-based photovoltaics (86.03), window retrofitting (88.83), and facade cladding (82.21) in all five key metrics of aesthetics, economic feasibility, safety, energy efficiency, and innovation. The findings indicate that CIGS technology exhibits not only exceptional visual adaptability but also attains balanced performance with regard to environmental and structural metrics. This renders it a highly competitive and comprehensive solution for sustainable building retrofits.